2021
DOI: 10.1111/apt.16381
|View full text |Cite
|
Sign up to set email alerts
|

Histological disease activity in patients with microscopic colitis is not related to clinical disease activity or long‐term prognosis

Abstract: Background: Microscopic colitis (MC) is a common cause of chronic watery diarrhea.Biopsies with characteristic histological features are crucial for establishing the diagnosis. The two main subtypes are collagenous colitis (CC) and lymphocytic colitis (LC) but incomplete forms exist. The disease course remains unpredictable varying from spontaneous remission to a relapsing course.Aim: To identify possible histological predictors of course of disease.Methods: Sixty patients from the European prospective MC regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although one might expect that the extent of inflammation, as measured by the percentage of lymphocytes, might correlate with symptoms, that has generally not been the case. Olsen et al ( 6 ) found that neither the total cell density in the lamina propria, proportion of CD3+ lymphocytes in the lamina propria, nor surface epithelium correlated with the number of daily stools or watery stools in 60 patients from a European prospective registry. Similarly, Shaz et al ( 24 ) found no association between symptoms and histologic findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one might expect that the extent of inflammation, as measured by the percentage of lymphocytes, might correlate with symptoms, that has generally not been the case. Olsen et al ( 6 ) found that neither the total cell density in the lamina propria, proportion of CD3+ lymphocytes in the lamina propria, nor surface epithelium correlated with the number of daily stools or watery stools in 60 patients from a European prospective registry. Similarly, Shaz et al ( 24 ) found no association between symptoms and histologic findings.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the number of intraepithelial lymphocytes and the thickness of the subepithelial collagen band, patients are classified as having lymphocytic or collagenous colitis. Both conditions have more intraepithelial lymphocytes, more than 20 for lymphocytic colitis and 10–20 for collagenous colitis ( 6 ). There are more lymphocytes in the lamina propria in both subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, the incidence and prevalence of this condition has risen, partly due to both greater awareness and increasing numbers of patients being diagnosed (2)(3)(4)(5). Diagnosis of MC is by colonoscopy, and histological analysis of multiple biopsy specimens collected along the colon is used to assess activity (6,7). However, heterogeneous immune profiles and disease characteristics among patients still make the pathogenesis of MC unclear (8,9).…”
Section: Editorial On the Research Topicmentioning
confidence: 99%